Assessment of the needs of youth in residential care: development and validation of an instrument - Calheiros, M. M. (2014)
This article presents the development of a Residential Care Youth Needs Assessment (RCYNA) instrument. In two studies, initial evidence regarding the RCYNA psychometric properties was obtained using a sample of youth in residential care. Results show adequate levels of content and face validity, reliability and concurrent validity.